2015
DOI: 10.5489/cuaj.3169
|View full text |Cite|
|
Sign up to set email alerts
|

Nightly sildenafil use after radical prostatectomy has adverse effects on urinary convalescence: Results from a randomized trial of nightly vs on-demand dosing regimens

Abstract: Introduction: This is a report on potency results from a randomized trial of nightly versus on-demand sildenafil after nerve-sparing radical prostatectomy (RP). A secondary objective was to analyze the effects of these sildenafil administration schemes on urinary health-related quality of life after RP. Methods: In total, 100 potent men were equally randomized to nightly and on-demand sildenafil 50 mg after minimally-invasive RP for 1 year. Health-related quality of life questionnaires were administered at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The concomitant use of VED in these studies is not clear, which adds another limitation to their interpretation. Also of interest is a follow-up study to the study by Pavlovich et al [172] suggesting poorer EPIC scores with nightly sildenafil 50 mg compared to PRN dosing, largely in the urinary irritative and bother subscales of the questionnaire [125]. Further study is required to clarify the implications of this report.…”
Section: Oral Pde 5 Inhibitorsmentioning
confidence: 81%
“…The concomitant use of VED in these studies is not clear, which adds another limitation to their interpretation. Also of interest is a follow-up study to the study by Pavlovich et al [172] suggesting poorer EPIC scores with nightly sildenafil 50 mg compared to PRN dosing, largely in the urinary irritative and bother subscales of the questionnaire [125]. Further study is required to clarify the implications of this report.…”
Section: Oral Pde 5 Inhibitorsmentioning
confidence: 81%
“…Studies have shown that PDE5i therapy after RARP may also improve urinary continence outcomes (19, 37, 38). Kaiho et al (24) showed that immediate PDE5i therapy may temporarily worsen immediate incontinence compared to late therapy.…”
Section: Discussionmentioning
confidence: 99%